Особенности синтеза структуры функционально-ориентированных технологических процессов комбинированной отделочной обработки осевых лезвийных инструментов - Михайлов, А. Н.; Михайлова, Е. А.; Маджид, А. Д. (НТУ "ХПІ", 2009)
In the given work weare developing a general approach and method for the synthesis of the technological finishing processes of axial cutting tools. They are based on morphological and functional-oriented synthesis of the rational structure of operations. In the work identifies specific structure of the technological process and completed its implementation. Investigation of some parameters of the functional elements for the axial cutting tools. Established an effective mechanical process.
Keywords: сверла; зенкеры; метчики; вакуумное ионно-плазменное покрытие